PENGARUH STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERWAWASAN MULTIKULTURAL - Miftahus Salam; Safira Sutan Atmaja (Journal Multicultural of Islamic Education, 2023)
The teaching learning process becomes effective when the teacher knows how to use the right approach. In the learning process, students should be encouraged to be able to think critically and can apply knowledge that has been acquired in the classroom and then be replicated in real life. Therefore, the existence of the right learning strategies can help teachers guide and enhance students’ critical thinking skills. One way to be able to develop critical thinking skills of learners by focusing on contextual teaching and learning. (CTL). This is a quantitative research method. Data collection methods use lifting, testing, observation and documentation. The population in this study was XI class pupils with random sampling. The data in this study was analyzed using a simple linear regression analysis method using the help of SPSS. The results of the study were obtained, first there is an influence between the learning strategy Contextual Teaching And Learning (CTL) on the critical thinking ability of students in the learning of Islamic Religious Education Class XI in SMA Negeri Tamanan Bondowoso. This, based on the test of the hypothesis using the simple linear regression test with the obtained value of Fcount of 15.127 with the significance level of 0,000 < 0.05, then Ho is rejected and Ha is accepted. Second, there is a significant influence of the Contextual Teaching And Learning (CTL) learning strategy on the critical thinking ability of students, it is based on a hypothetical test using a simple linear regression test with a significant value of 0,000 < 0.05 and tcount value of 3.889 > ttable of 2.024, then Ho is rejected and Ha is accepted.